Expression of the Metalloproteinase ADAM8 Is Upregulated in Liver Inflammation Models and Enhances Cytokine Release In Vitro. (11th March 2021) - Awan, Tanzeela; Babendreyer, Aaron; Wozniak, Justyna; Alvi, Abid Mahmood; Sterzer, Viktor; Cook, Lena; Bartsch, Jörg W.; Liedtke, Christian; Yildiz, Daniela; Ludwig, Andreas
Abstract : Acute and chronic liver inflammation is driven by cytokine and chemokine release from various cell types in the liver. Here, we report that the induction of inflammatory mediators is associated with a yet undescribed upregulation of the metalloproteinase ADAM8 in different murine hepatitis models. We further show the importance of ADAM8 expression for the production of inflammatory mediators in cultured liver cells. As a model of acute inflammation, we investigated liver tissue from lipopolysaccharide- (LPS-) treated mice in which ADAM8 expression was markedly upregulated compared to control mice. In vitro, stimulation with LPS enhanced ADAM8 expression in murine and human endothelial and hepatoma cell lines as well as in primary murine hepatocytes. The enhanced ADAM8 expression was associated with an upregulation of TNF- α and IL-6 expression and release. Inhibition studies indicate that the cytokine response of hepatoma cells to LPS depends on the activity of ADAM8 and that signalling by TNF- α can contribute to these ADAM8-dependent effects. The role of ADAM8 was further confirmed with primary hepatocytes from ADAM8 knockout mice in which TNF- α and IL-6 induction and release were considerably attenuated. As a model of chronic liver injury, we studied liver tissue from mice undergoing high-fat diet-induced steatohepatitis and again observed upregulation of ADAM8 mRNA expression compared to healthy controls. In vitro, ADAM8 expression was upregulated in hepatoma, endothelial, and stellate cell lines by various mediators of steatohepatitis including fatty acid (linoleic-oleic acid), IL-1 β, TNF- α, IFN- γ, and TGF- β . Upregulation of ADAM8 was associated with the induction and release of proinflammatory cytokines (TNF- α and IL-6) and chemokines (CX3CL1). Finally, knockdown of ADAM8 expression in all tested cell types attenuated the release of these mediators. Thus, ADAM8 is upregulated in acute and chronic liver inflammation and is able to promote inflammation by enhancing expression and release of inflammatory mediators.